EFFECTIVENESS OF USING THE SAYGO-LEARN APPLICATION IN LONG DISTANCE HISTORY LEARNING - Dini, Devvi Wahyu Wulan; Sunardi, Sunardi; Widiarto, Tri (Jurusan Pendidikan Sejarah, Universitas Halu Oleo, 2020)
Learning is the most important part in the world of education. The Covid-19 pandemic has hampered the learning process. The ministry suggestion to impose distance learning has resulted in various schools changing the procedures for the learning process. One of the schools in Demak Regency, namely SMK Negeri 1 Sayung, created a software-based application to overcome distance history learning during the Covid-19 pandemic. The application is known as Saygo-Learn. saygo-Learn functions as a distance learning tool that contains learning materials and assignments for students. The use of the Saygo-Learn application is considered effective in improving student learning outcomes. the distance history learning process using Saygo-Learn also helps educators to foster the development of students when participating in the distance history learning process.Â